Effects of pruning intensity and plant growth regulators on growth, yield and quality of guava (Psidium Guajava L.) CV. Sardar (Bangladesh Journal of Botany, 2023)
Effects of pruning intensity and spray of plant growth regulators (PGR) on dfferent parameters of Guava (Psidium Guajava L.) Sardar were investigated. Growth, quality and yield attributing characters were improved at 30 cm pruning intensity. With respect to effect of plant growth regulators, application of 600 ppm NAA improved all the characters except  minimum number of days taken to flower initiation (39.47), acidity (0.33 %), TSS (12.11 oBrix) and total sugars (6.79 %) which were recorded in 600 ppm ethephon. The interaction studied showed that P3G2 (30 cm pruning + 600 ppm NAA) had recorded the highest value with growth, yield and quality, while the combination of P3G3 (30 cm pruning + 600 ppm ethephon) was good for qualitative parameters.Bangladesh J. Bot. 52(3): 813-820, 2023 (September)